A community for students.
Here's the question you clicked on:
 0 viewing
Barrelracing
 one year ago
Solve 3x2 + 6x + 15 = 0
−1 ± i
− 1 ± 2i
−2 ± i
−2 ± 2i
Barrelracing
 one year ago
Solve 3x2 + 6x + 15 = 0 −1 ± i − 1 ± 2i −2 ± i −2 ± 2i

This Question is Closed

SolomonZelman
 one year ago
Best ResponseYou've already chosen the best response.0\(\large\color{black}{ \displaystyle x^2+2x+1=(x+1)^2 }\) \(\large\color{black}{ \displaystyle 3(x^2+2x+1)=3x^2+6x+9=3(x+1)^2 }\) *~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~* \(\large\color{black}{ \displaystyle 3x^2+6x+15=0 }\) \(\large\color{black}{ \displaystyle 3x^2+6x+9+6=0 }\) \(\large\color{black}{ \displaystyle 3x^2+6x+9=6 }\) \(\large\color{black}{ \displaystyle 3(x+1)^2=6 }\) \(\large\color{black}{ \displaystyle (x+1)^2=2 }\)

SolomonZelman
 one year ago
Best ResponseYou've already chosen the best response.0and then proceed by taking the square root of both sides and solving for x.
Ask your own question
Sign UpFind more explanations on OpenStudy
Your question is ready. Sign up for free to start getting answers.
spraguer
(Moderator)
5
→ View Detailed Profile
is replying to Can someone tell me what button the professor is hitting...
23
 Teamwork 19 Teammate
 Problem Solving 19 Hero
 Engagement 19 Mad Hatter
 You have blocked this person.
 ✔ You're a fan Checking fan status...
Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.